CIPP’S Model of Curriculum Evaluation Focused on the Arabic Reading Skills Textbook KSKK 2019 - Aini, Karima Ayu Nur; Inayah, Inayah; Ismail, Ismail (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
Curriculum evaluation is a strategic step to assess the effectiveness of a learning program. This study aims to evaluate the 2019 KSKK grade VIII Arabic textbook, specifically in terms of reading skills (maharah qira'ah), using the CIPP (Context, Input, Process, Product) evaluation model. A qualitative approach with an explanatory design was used to analyze the alignment of the textbook's content with student needs, the curriculum, the learning process, and the outcomes achieved. The data were obtained through document analysis of the 2019 KSKK Grade VIII Arabic textbook used at MTs Miftahussa’adah Mijen Semarang, KSKK curriculum policy documents, textbook development guidelines, scientific journals, reference books, and other relevant supporting documents, focusing on reading texts, learning activities, exercises, and evaluation components related to maharah qira'ah. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing to identify patterns, relationships, and areas for improvement. The evaluation results indicate that the textbook is contextually relevant, has systematic content appropriate to students' ability levels, and supports the development of reading skills. However, the textbook still requires additional learning media to enrich students' learning experiences. The CIPP model has proven effective in providing a comprehensive overview of the strengths and areas for improvement of the textbook. Therefore, this book is suitable for use as a teaching resource in effective, contextual, and integrated Arabic language learning.